DEVELOPMENT, PHYSICO-CHEMICAL AND MICROBIOLOGICAL CHARACTERIZATION OF A CUBE BROTH BASED ON "LANHOUIN" STABILIZED USING PLANT EXTRACTS - ALLAGBE, Aymard Constantin; DEGNON, René Gnimabou; KONFO, Christian T. R. (My University, 2020)
The present study aims to limit the consumption of synthetic broths by developing a natural broth based on ―lanhouin‖ flour stabilized with plant extracts for their antifungal and antioxidant activities.To do this, the essential oils of Pimenta racemosa, Cymbopogon citratus and the powder of Curcuma longa were used at different doses. The physico- chemical characterization of the samples of cube broths produced indicates that these latter have a water content of varied from 45.52 to 50.54% and pH varying from to 6.82 and 7.58. Microbiological analyzes revealed the presence of total mesophilic flora and Staphylococcus spp in all samples. The Sulfito-Reducing Anaerobes (ASR) were counted in 05 samples out of 13 analyzed. The fungal flora was present in 03 samples out of 13 analyzed. On the other hand, there is a total absence of total coliforms in the different samples. It then becomes necessary to assess the acceptability of the innovative product developed with a view to its future development
Keywords: Food Broth; cube; "Lanhouin"; Plant; Extracts; Innovation